A guide to the winged aphids (Homoptera) of Costa Rica - Voegtlin, David (2003)
This guide is a compilation of limited morphological and biological information on the winged morphs of 60 species of aphids that have been collected in Costa Rica. It should not be viewed as a definitive taxonomic treatise on the aphids of Costa Rica, rather it is a tool that can be used to assist in research on the biology, host plant relationships, taxonomy, and virus transmission capabilities of aphids. Each species is covered in an identical manner. Morphological and biological information is provided in both Spanish and English as well as photographs of slide mounted specimens. Keys are provided to help the user in identifying the species. Most of the specimens examined were taken in traps associated with epidemiological studies. Limited field collecting has generated host records and these have been added to a list of the aphids of Central America that was compiled by Pamela Anderson and appended in the guide with her permission. The authors hope that this book will be useful to entomologists in Costa Rica and Central America.